2018
DOI: 10.1159/000493655
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Reduces Acetaminophen-Induced Liver Injury by Activating the Nrf2 Antioxidative Defense System via the AMPK/Akt/GSK3β Pathway

Abstract: Background/Aims: Pterostilbene (Pts), a natural dimethylated analog of resveratrol from blueberries, exerts antioxidative and anti-apoptotic effects in various diseases. This study aims to investigate the protective effects and mechanism of Pts against acetaminophen (APAP)-induced hepatotoxicity in vivo. Methods: C57BL/6 mice were treated with APAP or APAP+Pts. HepG2 cells were used to further explore the underlying mechanisms in vitro. The effects of Pts on hepatotoxicity were measured by commercial kits, Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…Increased content of LPO and diminish enzymes activities such as SOD, CAT, GR, GPx and level of GSH were noticed in APAP group. In support of our data, previously reported work showed that APAP encourages oxidative stress and impairment of the antioxidant system of the liver [ 42 , 43 ]. While rats treated with CO reveal remarkable improvement in the activity of the antioxidant enzymes, GSH level and suppresses high level LPO in APAP group.…”
Section: Discussionsupporting
confidence: 92%
“…Increased content of LPO and diminish enzymes activities such as SOD, CAT, GR, GPx and level of GSH were noticed in APAP group. In support of our data, previously reported work showed that APAP encourages oxidative stress and impairment of the antioxidant system of the liver [ 42 , 43 ]. While rats treated with CO reveal remarkable improvement in the activity of the antioxidant enzymes, GSH level and suppresses high level LPO in APAP group.…”
Section: Discussionsupporting
confidence: 92%
“…The antioxidant capability of Pter has been previously shown in several experimental models [37,38,[55][56][57][58] and our results well agree with the previously reported effect of Pter on NRF2 activation [37,38,57], one of the main redox homeostasis regulators and an appealing therapeutic target for DR [59]. Under physiological conditions, NRF2 is sequestered mostly in the cytosol and degraded through ubiquitination.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, as Pter administration does not influence body weight and blood glucose levels, any beneficial effects should be attributed to a direct effect of Pter on the retina. The demise of retinal neural cells may be induced by hyperglycaemia-generated hydrogen peroxide [54], and Pter reduces its cytotoxicity, oxidative stress and apoptosis in different cellular models like HepG2 cells [55]. According to our results, Pter decreased the hydrogen peroxide production induced by high glucose levels in vivo ( Figure 3D) and in vitro ( Figure 5C).…”
Section: Discussionsupporting
confidence: 55%
“…AKT is a crucial metabolic regulation enzyme that participates in the maintenance of regulating cellular metabolism to cellular energy homeostasis. It plays a protective role in an APAP-induced mouse model by promoting cell survival, oxidative stress responses, and energy generation [54,55]. mTOR is a master kinase regulating the synthesis and metabolism of protein and lipid.…”
Section: Discussionmentioning
confidence: 99%